IMPLEMENTATION CHEERLEADERS GAME TO IMPROVE NOUN SPEECH READING COMPETENCE TOWARD CHILDREN WITH HEARING IMPAIRMENT (Proceedings of International Conference on Special Education, 2015)
Children with hearing impairment experience problem in verbal communicating, between language and speech. That condition impact from impairment of hearing organ’s. When reading speech, kids sometime having a problem reading articulation from opposite who have a talk with. This research aim to discover if there is a impact from a cheerleaders game when increase the ability of reading noun speech to children with hearing impairment. Cheerleaders game are series of activity to integrate several of sensory sense when speech noun with varied moving movement. This research using experiment method with design research one group pretest – post test and also data processing with Wilxocon test. Research samples are 6 students with hearing impairment at third grade from SLB X. The instrument that used are reading noun speech ability test. Result from data analyzed shows that cheerleaders game application gave a relatively huge contribution at intensify noun speech reading ability is 38,34%, so that cheerleaders game can be used by teacher as an studying alternative in improving noun speech reading ability to children with hearing impairment in SLB. Measurement with Wilxocon got J hitung = 21 so J tabel = 0,  that H0 refused because J hitung > J tabel , with the hypothesis that represented at the research can be accepted. This research can be reviewed more with other researcher with sample research that relatively considerable, vocabulary and movement more varied that are adapted with needs,  lack of ability also children competence.